First record of the fruit fly, Diarrhegma modestum (Fabricius) (Diptera: Tephritidae) from Bangladesh - Hossain, M Aftab; Khan, Shakil A (Bangladesh Journal of Zoology, 2015)
Abstract not available Bangladesh J. Zool. 41(2): 265-267, 2013